State payments to victims of violent crime: discretion and bias in awards for sexual offences - Daly, Kathleen (The British journal of criminology, 2019)
State monetary schemes for victims of violent crime began in the 1960s and operate in 35 countries today, yet knowledge is lacking on who is applying, how decisions are reached, variation in awards and why amounts may differ. Analysing 291 sexual offence cases in Queensland, we ask whether awards differ by victim sex/gender and by societal constructs of ideal, real rape, and credible victims. We found that male child victims received higher awards than female child victims for more serious sexual offences and that awards to females aged 12 and older were affected by elements associated with real rape and credible victims. We call upon researchers and governments to pursue and expand this new area of research.